Increasing Inhibition of the Rat Brain 2-Oxoglutarate Dehydrogenase Decreases Glutathione Redox State, Elevating Anxiety and Perturbing Stress Adaptation - Artem V. Artiukhov; Anastasia V. Graf; Alexey V. Kazantsev; Alexandra I. Boyko; Vasily A. Aleshin; Alexander L. Ksenofontov; Victoria I. Bunik (MDPI AG, 2022)
Specific inhibitors of mitochondrial 2-oxoglutarate dehydrogenase (OGDH) are administered to animals to model the downregulation of the enzyme as observed in neurodegenerative diseases. Comparison of the effects of succinyl phosphonate (SP, 0.02 mmol/kg) and its uncharged precursor, triethyl succinyl phosphonate (TESP, 0.02 and 0.1 mmol/kg) reveals a biphasic response of the rat brain metabolism and physiology to increasing perturbation of OGDH function. At the low (TE)SP dose, glutamate, NAD+, and the activities of dehydrogenases of 2-oxoglutarate and malate increase, followed by their decreases at the high TESP dose. The complementary changes, i.e., an initial decrease followed by growth, are demonstrated by activities of pyruvate dehydrogenase and glutamine synthetase, and levels of oxidized glutathione and citrulline. While most of these indicators return to control levels at the high TESP dose, OGDH activity decreases and oxidized glutathione increases, compared to their control values. The first phase of metabolic perturbations does not cause significant physiological changes, but in the second phase, the ECG parameters and behavior reveal decreased adaptability and increased anxiety. Thus, lower levels of OGDH inhibition are compensated by the rearranged metabolic network, while the increased levels induce a metabolic switch to a lower redox state of the brain, associated with elevated stress of the animals.